Results of the European Photo International Cross-comparison Course as part of the quality assurance of the crown condition assessment 2015 (Photo ICC 2015) - Stefan Meining; Yvonne Morgenstern; Nicole Wellbrock; Nadine Eickenscheidt (Johann Heinrich von Thünen-Institut, 2016)
Photo ICCs represent one of different measures for quality assurance of the crown condition survey, which is part of the European forest monitoring. The European Photo ICC 2015 took place between June 23rd and September 29th and was carried out for the three regions Northern, Central and Mediterranean Europe. In total 123 teams participated. The defoliation and assessable crown were assessed on the basis of photos for all main tree species of one region. Half of the photos had already been used at the Photo ICC 2010. The mean deviation of the countries from the weighted median of all countries of one region was evaluated as well as the occurrence of outliers and the specification of the assessable crown. The repeatedly used photos further enabled the evaluation of the assessment continuity. The results reveal a good homogeneity of the defoliation assessment within Europe. The mean deviation of the countries usually lay within a ±10%-interval and most countries only showed few outliers. For some regions and tree species, however, systematic differences in the defoliation assessment among countries were observed. Countries participating in the Photo ICC for two regions, in general displayed the same trend for both regions. Differences in the definition of the assessable crown did not result in larger deviations regarding the defoliation assessment. In Central Europe, the defoliation of beech (Fagus sylvatica) and oak (Quercus robur und Q. petraea) was significantly higher for the same photos in 2015 than in 2010. This observation existed for almost all participating countries. Several reasons for this increase are possible like differences in the quality of the printed photos or varying experience of teams in the defoliation assessment. No significant differences between 2010 and 2015 were found for the investigated tree species of Northern and Mediterranean Europe as well as for the coniferous tree species of Central Europe. The results of the Photo ICC 2015 underline the need to carry out photo courses as regular quality assurance in the crown condition survey. The advantages include the reproducibility of results, the option of testing the continuity of assessment, participation of a larger number of teams and saving of costs and time. Thus, Photo ICCs represent a useful addition to nation-wide and European-wide Field ICCs to ensure data quality in the crown condition survey. – – Photo-ICCs stellen eine von verschiedenen Maßnahmen zur Qualitätssicherung der Kronenzustandsansprache im Rahmen des europaweit stattfindenden Forstlichen Umweltmonitorings dar. Der europäische Photo-ICC 2015 wurde im Zeitraum vom 23.06. bis 29.09.2015 für die drei Regionen Nord-, Mittel- und Südeuropa durchgeführt. Insgesamt haben 123 Teams an dem Photo-ICC 2015 teilgenommen. Anhand von Fotos wurden die Kronenverlichtung und der Boniturbereich der jeweiligen Hauptbaumarten einer Region bestimmt. Die Hälfte der Fotos fand bereits im Photo-ICC 2010 Verwendung. Bewertet wurde die mittlere Abweichung der Länder vom gewichteten Median aller Länder einer Region, das Vorkommen von Ausreißern sowie die Wahl des Boniturbereichs. Die Wiederholungsfotos ermöglichten außerdem eine Aussage über die Schätzkontinuität. Die Ergebnisse belegen insgesamt eine gute Homogenität der Kronenzustandsansprache innerhalb Europas. Die mittleren Abweichungen bewegten sich i.d.R. im ±10%-Abweichungsbereich und die meisten Länder wiesen nur wenige Ausreißer auf. Allerdings konnten auch systematische Abweichungen einzelner Länder beobachtet werden. Länder die am Photo-ICC für zwei Regionen teilgenommen haben, zeigten meist den gleichen Trend für beide Regionen. Die unterschiedliche Definition des Boniturbereichs führte nicht zu deutlichen Änderungen in der Bewertung der Kronenverlichtung. In Mitteleuropa wurde die Kronenverlichtung der Buche (Fagus sylvatica) und Eiche (Quercus robur und Q. petraea) für dieselben Fotos und für fast jedes teilnehmende Land 2015 signifikant höher eingeschätzt als 2010. Diese Beobachtung kann verschiedene Gründe haben z.B. Unterschiede in der Druckbildqualität oder unterschiedliche Erfahrung in der Ansprache der Teams. Für die betrachteten Baumarten Nord- und Südeuropas sowie für die Nadelbäume Mitteleuropas wurden keine signifikante Abweichung in der Bewertung gefunden. Die Ergebnisse des Photo-ICC 2015 unterstreichen die Notwendigkeit, Photo-ICCs als regelmäßige Qualitätssicherungsmaßnahme in der Kronenzustandsaufnahme durchzuführen. Photo-ICCs sind durch die Reproduzierbarkeit der Ergebnisse, durch die Überprüfung der Schätzkontinuität und durch die hohe Erreichbarkeit teilnehmender Aufnahmeteams in Ergänzung zu den Feld-Schulungen auf Landes- und Europaebene eine sinnvolle Ergänzung zur Sicherung der Datenqualität in der Kronenzustandserhebung.
urn:nbn:de:gbv:253-201607-dn057012-8
Keywords: 630; defoliation; crown condition survey; forest monitoring; quality assurance; international cross-comparison course; Kronenverlichtung; Kronenzustandserhebung; Forstliches Umweltmonitoring; Qualitätssicherung; internationaler Foto-Vergleichskurs